Pengendalian Internal Pengelolaan Retribusi Objek Wisata pada Dinas Pariwisata Kabupaten Lombok Tengah - Wali, Fahrul Imam Kasimpa; Pusparini, Herlina; Lenap, Indria Puspitasari (Fakultas Ekonomi dan Bisnis Unram, 2025)
This study aims to analyze the implementation of the internal control system in the management of tourist attraction levies in the Tourism Office of Central Lombok Regency and to assess its compliance with Government Regulation No. 60 of 2008 concerning the Government Internal Control System. The research method used is descriptive with a qualitative approach, with data collection techniques through interviews, observations, and documentation. The informants in this study were the Head of Finance, Head of Development, and Assistant Treasurer of Revenue. The results of the study indicate that the implementation of internal control of tourism retribution management has covered several aspects of the government's internal control system, such as the control environment, risk assessment, control activities, information and communication, and monitoring. However, there are still several obstacles, such as less than optimal internal monitoring, and limited information technology resources. This study concludes that although the internal control system has been implemented, it is not fully in accordance with PP No. 60 of 2008. Therefore, improvements are needed in strengthening the control structure, increasing human resource capacity, and utilizing technology to improve accountability and transparency in the management of tourist attraction levies.